2002
DOI: 10.4049/jimmunol.168.1.232
|View full text |Cite
|
Sign up to set email alerts
|

CD5-Negative Regulation of B Cell Receptor Signaling Pathways Originates from Tyrosine Residue Y429 Outside an Immunoreceptor Tyrosine-Based Inhibitory Motif

Abstract: CD5 is a cell surface receptor that negatively regulates B cell function, but whose relationship to the immunoreceptor tyrosine-based inhibitory motif (ITIM) family of B cell inhibitory receptors is unclear. Using Fcγ type IIB receptor-CD5 chimeras encompassing the cytoplasmic domain of CD5, we previously showed that a particular region of the molecule containing two tyrosine residues, Y429 and Y441, in an amino acid stretch similar to the Src autophosphorylation motif and a putative ITIM, respectively, antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 60 publications
3
42
0
Order By: Relevance
“…We have however observed that, contrary to the majority of CD5 À B cells, normal CD5 þ blood B cells displayed a low Ca 2 þ response following anti-IgM stimulation, 15 confirming the role of CD5 as a negative regulator of BCR signaling. 16,17 Even though BCR-mediated activation is often deficient in CLL, CD5 may act independently of the BCR by recruiting signaling molecules, 18,19 and eliciting the production of B-cell survival factors such as interleukin (IL)-10. 15 IL-10 is indeed produced by most CLL B-cells, 20 improves the survival of malignant CLL B-cells, 21 and IL-10 serum levels in CLL correlated with the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…We have however observed that, contrary to the majority of CD5 À B cells, normal CD5 þ blood B cells displayed a low Ca 2 þ response following anti-IgM stimulation, 15 confirming the role of CD5 as a negative regulator of BCR signaling. 16,17 Even though BCR-mediated activation is often deficient in CLL, CD5 may act independently of the BCR by recruiting signaling molecules, 18,19 and eliciting the production of B-cell survival factors such as interleukin (IL)-10. 15 IL-10 is indeed produced by most CLL B-cells, 20 improves the survival of malignant CLL B-cells, 21 and IL-10 serum levels in CLL correlated with the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been demonstrated that CD5 is rapidly recruited and colocalized with the TCR/CD3 complex at the immune synapse (7), and that it inhibits TCR signaling in T lymphocytes interacting with APC without influencing conjugate formation (8). Furthermore, it has been reported that CD5-mediated inhibition of TCR signaling does not require the CD5 extracellular domain, but only its cytoplasmic tail (9), in which a pseudo-ITAM is likely to play a role (8,10). Therefore, interaction of CD5 with its ligand does not seem to be necessary for TCR signaling inhibition.…”
mentioning
confidence: 99%
“…Although we found that B-1 cells lack Lck, we also found that B-1 cells express phosphorylated CD5, and so the latter may, as reported by others (12,13,19), play a key role in blocking BCR signaling in B-1 cells, presumably after phosphorylation by another src kinase. Recently, however, Bondada and colleagues reported that BCR signaling is defective in peritoneal B-1b cells that lack CD5 (30), indicating that abnormal BCR signaling takes place in the absence of CD5 in this B-1 cell subset.…”
Section: Bcr Signaling Is Defective In B-1 Cellsmentioning
confidence: 38%
“…As noted above, it has been suggested that the phosphorylated form of CD5 is responsible for blocked BCR signaling, and that high levels of Lck are responsible for constitutive CD5 phosphorylation, in naive B-1 cells (13,22). Because B-1 cells express little, if any, Lck, it was of interest to determine whether B-1 cells contain phosphorylated CD5.…”
Section: Bcr Signaling Is Defective In B-1 Cellsmentioning
confidence: 99%
See 1 more Smart Citation